New Policies, New Technologies : Modelling the Potential for Improved Smear Microscopy Services in Malawi - Ramsay, A. (2012)
BACKGROUND: To quantify the likely impact of recent WHO policy recommendations regarding smear microscopy and the introduction of appropriate low-cost fluorescence microscopy on a) case detection and b) laboratory workload. METHODOLOGY/PRINCIPAL FINDINGS: An audit of the laboratory register in an urban hospital, Lilongwe, Malawi, and the application of a simple modelling framework. The adoption of the new definition of a smear-positive case could directly increase case detection by up to 28%. Examining Ziehl-Neelsen (ZN) sputum smears for up to 10 minutes before declaring them negative has previously been shown to increase case detection (over and above that gained by the adoption of the new case definition) by 70% compared with examination times in routine practice. Three times the number of staff would be required to adequately examine the current workload of smears using ZN microscopy. Through implementing new policy recommendations and LED-based fluorescence microscopy the current laboratory staff complement could investigate the same number of patients, examining auramine-stained smears to an extent that is equivalent to a 10 minutes ZN smear examination. CONCLUSIONS/SIGNIFICANCE: Combined implementation of the new WHO recommendations on smear microscopy and LED-based fluorescence microscopy could result in substantial increases in smear positive case-detection using existing human resources and minimal additional equipment.